2001
DOI: 10.3201/eid0705.010008
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Consequences and Cost of Limiting Use of Vancomycin for Perioperative Prophylaxis: Example of Coronary Artery Bypass Surgery

Abstract: Routine use of vancomycin for perioperative prophylaxis is discouraged, principally to minimize microbial resistance to it. However, outcomes and costs of this recommendation have not been assessed. We used decisionanalytic models to compare clinical results and cost-effectiveness of no prophylaxis, cefazolin, and vancomycin, in coronary artery bypass graft surgery. In the base case, vancomycin resulted in 7% fewer surgical site infections and 1% lower all-cause mortality and saved $117 per procedure, compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
0
7
0
1
Order By: Relevance
“…In addition, short exposures to glycopeptides for prophylaxis in non-MRSA patients are far less likely to promote resistance than prolonged treatments, especially for MRSA infections. We recently developed a decision-analytic model to calculate the clinical benefits and costs associated with the use of either cefazolin or vancomycin for prophylaxis in coronary artery bypass surgery (Zanetti et al 2001). In the base case, where 40% of S. aureus and 80% of coagulase-negative staphylococci were resistant to methicillin, cefazolin had to be 25% better than vancomycin against susceptible organisms in order to be more effective.…”
Section: Systemic Perioperative Prophylaxis With Antibiotic Active Agmentioning
confidence: 99%
“…In addition, short exposures to glycopeptides for prophylaxis in non-MRSA patients are far less likely to promote resistance than prolonged treatments, especially for MRSA infections. We recently developed a decision-analytic model to calculate the clinical benefits and costs associated with the use of either cefazolin or vancomycin for prophylaxis in coronary artery bypass surgery (Zanetti et al 2001). In the base case, where 40% of S. aureus and 80% of coagulase-negative staphylococci were resistant to methicillin, cefazolin had to be 25% better than vancomycin against susceptible organisms in order to be more effective.…”
Section: Systemic Perioperative Prophylaxis With Antibiotic Active Agmentioning
confidence: 99%
“…10 Prolonged antimicrobial administration can be harmful to patients by promoting antimicrobial-resistant bacteria and increasing the incidence of antibiotic-associated complications. 2,14 Prophylaxis using routine vancomycin resulted in fewer deep and superficial SSIs and fewer deaths compared with routine cefazolin for CABG surgery. 2 About a third (34%) of patients undergoing cardiac surgery had their antimicrobial prophylaxis discontinued within 24 hours of completion of surgery.…”
Section: Antibiotic Prophylaxis Protocolsmentioning
confidence: 99%
“…12, 13 Research has found that only 70% of cardiac surgery patients received cefazolin (Ancef), and only 60% received antibiotics 1 hour or less prior to surgical incision. 14 Additional concerns regarding antimicrobial resistance were found.…”
Section: Antibiotic Prophylaxis Protocolsmentioning
confidence: 99%
“…This study assessed outcomes and costs associated with discouraging the routine use of vancomycin as a perioperative prophylaxis 1 . A cost‐effectiveness analysis using a hypothetical cohort of 10,000 patients undergoing coronary artery bypass grafting procedures was conducted.…”
Section: Using Vancomycin For Perioperative Prophylaxismentioning
confidence: 99%